BUSINESS DEVELOPMENT STRATEGY OF HYDROPONIC MELON (CUCUMIS MELO L.) PRODUCTION AT PT INDIGEN KARYA UNGGUL THROUGH BUSINESS MODEL CANVAS - Arifin, Zainal; Ananda Noor Lailya, Ma’arifa Putri (This journal is published by the Vocational School of Universitas Sebelas Maret., 2000)
The purpose of this research is to find the obstacles and threats that hinder the melon production process at PT Indigen Karya Unggul, formulate new strategies based on the advantages and opportunities owned by the company by minimizing the shortcomings and threats that exist, and create a new business model canvas prototype that can be applied by the company in the context of business development. The data collection technique that researchers apply is the interview and observation method accompanied by direct interviews. The type of research chosen is qualitative research. The analysis of the business development strategy that can be applied by the company with the new business model canvas prototype is the addition of human resources to run the existing business lines needs to be done so that existing human resources can be specialized according to the field of work so that the targets of each business line can be realized. In addition, PT Indigen Karya Unggul can use the new business model canvas prototype in carrying out its business activities. Especially in the customer segment block, including by expanding the intended market segment, reaching markets that have not been reached before, and creating attractive and creative marketing content.